THE MEDIA AND SOCIO-POLITICAL CHANGE: A SNAPSHOT OF NORTH AFRICA AND GHANA’S CASE - Samuel Adu-Gyamfi; Kwasi Amakye-Boateng; Richard Oware (Paramita: Historical Studies Journal)
The mass media is a very useful tool to educate, to inform and to entertain. However, recent studies have shown that the media in whatever form has contributed immensely to bring about both social and political change in respective communities across the globe and Africa in particular. The case of Ghana has been presented from the different tangents by different authors. Significantly, this contribution pays attention to the role of the press (media) as well as the digital media in ensuring effective social and political change. In the first instance, this looks at the role of the media from the past to present and juxtaposes that with recent developments in Ghana and other African Countries. Attention is also paid to the role of the media in the respective elections in Ghana.